Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1161/circoutcomes.114.001612
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Recognition and Healthcare Experiences of Young Women With Acute Myocardial Infarction

Abstract: Background Prompt recognition of acute myocardial infarction (AMI) symptoms and timely care-seeking behavior are critical to optimize acute medical therapies. Relatively little is known about the symptom presentation and care-seeking experiences of women aged ≤55 years with AMI, a group shown to have increased mortality risk as compared with similarly aged men. Understanding symptom recognition and experiences engaging the healthcare system may provide opportunities to reduce delays and improve acute care for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
99
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 44 publications
2
99
0
5
Order By: Relevance
“…10,11) A previous study also indicated that young women were more likely to have CAD without chest pain. 12) Another study in a Canadian cohort of patients whose age was under 55 years with acute coronary syndrome supported this pattern. 13) Our study showed that 48.88% of postmenopausal cases were identified as ACS, compared to 82.46% of premenopausal patients identified as ACS.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…10,11) A previous study also indicated that young women were more likely to have CAD without chest pain. 12) Another study in a Canadian cohort of patients whose age was under 55 years with acute coronary syndrome supported this pattern. 13) Our study showed that 48.88% of postmenopausal cases were identified as ACS, compared to 82.46% of premenopausal patients identified as ACS.…”
Section: Discussionmentioning
confidence: 91%
“…19) There were relatively few narrowed segments of coronary arteries in younger women compared with women over 50 years of age. 12) This was probably because young women were more likely to have inflammation, coronary spasm, plaque erosion, or rupture. The clinical manifestations of postmenopausal patients were more complex, and collateral circulation was easily formed as they had a longer disease duration and long-term progress of the disease course.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive evaluations have suggested that these discrepancies are multifactorial 5. They are partly explained by clinical differences where women with ACS are older at presentation, have a higher burden of comorbidities, and tend to present later and with more atypical symptoms compared with men 3, 6, 7, 8, 9, 10. In addition, there are sex‐based differences in the primary and secondary treatment of coronary disease 11, 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Researchers have also shown that gender differences exist in regards to acute myocardial infarction and heart failure symptom recognition among women, and reperfusion and preventive therapies remain underutilized in women, which may also account for their increased mortality. [11][12][13][14][15][16] Yet, the fact remains that women are transplanted less frequently than men, making it critical for researchers to examine why such gender differences continue to exist. Since men and women who have already undergone an OHT should theoretically have similar cardiac illness profiles, examining clinical characteristics and outcomes in those who have undergone OHT may shed light on this continued gender disparity.…”
Section: Introductionmentioning
confidence: 99%